Do posture correction exercises have to be boring? Using unstable surfaces to prevent poor posture in children - Jankowicz-Szymanska, Agnieszka; Mikolajczyk, Edyta (Medical Studies/Studia Medyczne, 2016)
Introduction: Poor posture in children is a common problem. It appears most often in early school-age children and, if not corrected, progresses quickly as they mature. Aim of the research: To find a method that can prevent poor posture, is effective and attractive for children, and can be used on a wide scale in state schools. Material and methods : Seventy-seven first year pupils were tested at the beginning and at the end of the school year. Nineteen children undertook corrective exercises using unstable surfaces; 41 children sat on sensorimotor pillows during classes; and 17 children were the control group. Body mass and body height were measured. Body mass index was calculated. The symmetry of the position of selected skeletal points was assessed: the acromions, lower angles of the scapulas, apexes of the iliac crests, antero-superior iliac spine, and postero-superior iliac spine using a Duometer electronic device. The differences between the groups and changes between the first and second study for each group were estimated. Results : In the first study there were no significant differences in quality of posture. In the second study a significant improvement was noted in symmetry of the shoulders, scapulas, and pelvis in children who sat on sensorimotor pillows, as well as the position of the iliac crests and iliac spines in children exercising regularly on unstable surfaces. Conclusions: Exercises using unstable surfaces and sitting on sensorimotor pillows during classes might be an effective alternative to traditional posture correction exercises.